Sulfur-containing dihydro-pyrrolo [60]fullerene derivatives via 1,3-dipolar cycloadditions of glycine imine esters to C60 - Elemes, Yiannis; Hirsch, Andreas; Ioannou, John (Tetrahedron, 2007)
C reacts thermally with 1,3-dipoles, formed in situ, from sulfide-bearing imines of glycine esters, and affords dihydro-pyrrolo [60]fullerene derivatives containing a vinylic sulfide group, which were isolated in good yields, and characterized with H and C NMR, FTIR, UV-vis spectroscopies, and with FAB, ESI mass spectrometries. The new derivatives contain a sulfide, an imine, and an ester functionality for further chemical transformations. Mechanistic considerations with regard to the loss of a mercaptan molecule in the course of the cycloaddition are deployed. © 2007 Elsevier Ltd. All rights reserved.